Kajian Efektivitas Pengendalian Banjir di DAS Torosik - Jansen, Dave; Jansen, Tommy; Hendratta, Liany Amelia (Sam Ratulangi University, 2017)
The catchment area of Torosik River exists in Pinolosian Bolaang Mongondow region, often make flooding in society area because the discharge flooding is more than Torosik River capacity. The reduction of flood discharge is carried over with river flowing of Torosik reach in existing condition and the exist of retention pond in upstream part of river and river normalization in downstream part, using HMS and HEC-RAS computation tools. The peak outflow of one retention pond results 88.5 m3/sec, two retention pond results 86.9 m3/sec, and 93.3 m3/sec for existing condition. River flow simulation of river normalization condition results average water surface level 12m , and existing condition results average water surface level 13m. The reduction of flood discharge in existing condition and the exist of two retention pond result 6.4 m3/sec, if it is conversed to the height of water surface with constant velocity then get the height of water is just 0.5m.The river normalization result of discharge reduction more than the exist of retention pond of the Torosik catchment area. Â Keywords: watershed,, catchment area, flood discharge, peak discharge, HMS-HECRAS.